THEME-RHEME AND THEMATIC PROGRESSION IN OBAMA'S SPEECH AND ITS TRANSLATION - Oktaviani, Mufti Rizky (2013)
The study entitled Theme-Rheme and Thematic Progression in Obama's Speech and Its Translation focuses on how a translator puts differences in worldview between the source and the target language text. The differences of worldview itself can be found by analyzing each sentence chosen by the translator. This study used Theme-Rheme and Thematic Progression method taken from the book entitled An Introduction to Systemic Functional Linguistics 2nd Edition (Eggins, 2004). The study shows that both texts use Participants as the most frequently used theme. However, the target language considers Participants much more important than the source language does. Meanwhile, for thematic progression analysis both texts use Theme Reiteration. It can be concluded that both texts tend to be monotonous. Penelitian ini berjudul Theme-Rheme and Thematic Progression in Obama's Speech and Its Translation berfokus pada bagaimana penerjemah menempatkan perbedaan pandangan antara sumber dan teks bahasa target. Perbedaan pandangan itu sendiri dapat ditemukan dengan menganalisis setiap kalimat yang dipilih oleh penerjemah. Penelitian ini menggunakan analisa Theme-Rheme dan metode Progresi Tematik yang diambil dari buku berjudul An Introduction to Systemic Functional Linguistics 2nd Edition (Eggins, 2004). Studi ini menunjukkan bahwa kedua teks menggunakan Peserta sebagai tema yang paling sering digunakan. Namun, bahasa target menganggap peserta jauh lebih penting daripada bahasa sumber. Sementara itu, untuk analisis perkembangan tematik, kedua teks menggunakan Pengulangan Tema (Theme Reiteration). Dengan demikian dapat disimpulkan bahwa kedua teks cenderung monoton.